KUALITAS AIR SUNGAI PELAWI DI DESA PELAWI KECAMATAN BABALAN KABUPATEN LANGKAT SUMATERA UTARA The Pelawi River Water Quality in Pelawi Village District Babalan Langkat Regency of North Sumatera Province - Endaiyana Libertyta; Yunasfi Djayus; Ani Suryanti (AQUACOASTMARINE, 2015)
Pelawi River is one of the small rivers in the area of Langkat Regency whose streams flow gets input wastes from agricultural activity, domestic and industry activities that may effect water quality. This research described The Pelawi River Water Quality in Pelawi Village District Babalan Langkat Regency of North Sumatera Province. Physics and chemical parameters were analyzed by the Storet method based on water quality standard required by Peraturan Pemerintah No. 82 Tahun 2001, while biological parameters (macrozoobenthos) were analyzed by Abudance and Biomass Comparison (ABC) curve. The location of sampling sites was done by Purposive Sampling method in three core areas are station 1 (agriculture activity), station 2 (domestic activity) and station 3 (industry activity). The result of this research is that the River Pelawi used Storet method and ABC curve showed that water quality in Pelawi River were classified slightly polluted until moderatelly polluted water. Relate of Peraturan Pemerintah No. 82 Tahun 2001 that the water quality standard of Pelawi River is Class III.Keywords : Water Quality, Macrozoobenthos, Pelawi River